The Use of Digital Literacy in Teaching English at Junior High Schools in Maros Regency - Mah, Aisyah Aminny; Weda, Sukardi; Abduh, Amirullah (Har Press Indonesia, 2023)
This research analyses how teachers use digital literacy and students' perception, especially using digital applications. The subjects were two English teachers who teach Junior High Schools in Maros Regency. They were taken by using deliberate or purposive sampling. Each teacher was from UPTD SMPN 28 Satu Atap Salenrang Maros and UPTD SMP 14 Tanralili Maros. The research instruments were an observation checklist and an interview. Based on data analysis, it gathered several results; first, the use of digital literacy, especially using digital applications in teaching English, is actualized in the main activity before and after the presentation of the lesson target and is also used as a final assessment of the lesson. Furthermore, the teachers have to make comprehension preparation for digital literacy, which leads to long time preparation. Second, the students in Maros Regency perceive that using digital applications is very important because it can help them learn and understand the material provided easily. They also perceive that using digital applications has positive and negative impacts. However, the students enjoy every learning process using digital applications. They involve themselves during the learning process and complete assignments on time. The findings also show some barriers perceived by the students. They indicate that barriers come from internal and external factors while using digital applications, including mobile phones' RAM capacity, inadequate internet networks, and a gradual understanding of digital applications.